﻿Level of hypertension treatment adherence during pandemic - Valentina Petkova; Anna Peneva; Kalina Andreevska; Emil Hristov; Daniela Grekova; Anna Todorova; Antoaneta Tsvetkova; Milen Dimitrov (Pensoft Publishers, 2023)
Adherence to antihypertensive medications is the cornerstone for achieving metabolic syndrome control. The aim of this study was to explore how the pandemic has affected the adherence of patients with high BP to prescribed antihypertensive drugs. This multicentre observational study utilized self-completed questionnaires among patients between June and November 2020. Overall, 842 patients were included in the study. The likelihood of adherence was assessed using the 5‐item version of the Medication Adherence Report Scale (MARS-5Professor Rob Horne). The average MARS score of the sample was 16.81, the median was 4.162, and the most common value was 3 (24.5% of respondents) for the patients treated during the pandemic. The study suggests that several sociodemographic factors but not the COVID pandemic play a role in treatment adherence.